2019
DOI: 10.1108/ijmf-03-2019-0094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ownership structure and ownership concentration on credit risk of Chinese commercial banks

Abstract: Purpose The purpose of this paper is to examine the effects of bank ownership structure and ownership concentration on credit risk. Design/methodology/approach Using panel data on a sample of 88 Chinese commercial banks, with 826 observations over a period of 2003–2018, this study has applied system generalised method of moments regression to examine the impact of bank ownership structure and ownership concentration on credit risk. This study has used two measures of credit risk, which are non-performing loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 126 publications
(224 reference statements)
0
14
0
4
Order By: Relevance
“…This term refers to the percentage of government ownership in the company. The results (Liu et al, 2019) concluded that banks with high government ownership have low credit risk. In the same line, Oteros et al (2019) conducted a study to investigate the relationship between corporate governance and risk behavior in MENA countries' banking sector.…”
Section: Government Ownershipmentioning
confidence: 92%
See 1 more Smart Citation
“…This term refers to the percentage of government ownership in the company. The results (Liu et al, 2019) concluded that banks with high government ownership have low credit risk. In the same line, Oteros et al (2019) conducted a study to investigate the relationship between corporate governance and risk behavior in MENA countries' banking sector.…”
Section: Government Ownershipmentioning
confidence: 92%
“…In context, Liu et al (2019) conducted a study on Chinese commercial banks, and found that the banks with higher private ownership concentration have higher credit risks. Vintil and Gherghina (2014) argued that banks dominated by high concentrated ownership would tend to enter into risky investments due to shareholders' willingness to take more risk to influence the market value of shares to achieve higher profitability.…”
Section: Concentration Ownershipmentioning
confidence: 99%
“…Yang Liu et al (2019) examined the effects of bank ownership structure and ownership concentration on credit risk in their study. Using panel data on a sample of 88 Chinese commercial banks with 1194 observations over a period of 2003-2018, this study employs system generalised method of moments regression to examine the impact of bank ownership structure and ownership concentration on credit risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2019, the economic growth of China was projected to be 6.2% due to a strong and stable traditional financial sector that could only be multiplied by the new 'One Belt One Road' initiative [4,5]. This tremendous current and future growth in the Chinese financial and banking sector requires a better understanding of their banking sector's systemic risk from a local and global standpoint [6,7] given the systemic risk spillover between China and other countries [8], especially that the growing Chinese economy cannot be sustained with fragile and backward banking infrastructure. In this paper, we intend to fill this gap by using three different distance-to-risk measures (Distance to default (DD), Distance to insolvency (DI), and Distance to capital (DC)) to empirically assess the domestic interbank linkages and systemic contagion in China, following the footsteps of [8,20].…”
Section: Introductionmentioning
confidence: 99%